Viability of probiotic strain Lactobacillus rhamnosus and its impact on sensory properties of cheesecake during storage at −20 °C and 4 °C. (December 2020) - Hasgucmen, Ceren Kutlu; Sengun, Ilkin Yucel
Abstract: This study aimed to evaluate the survival of Lactobacillus rhamnosus HN001 inoculated in cheesecake during storage period and to detect the possibility of producing probiotic cheesecake by using healthy formulation. The produced cheesecake samples were investigated in terms of microbiological (total coliform, Escherichia coli, Staphylococcus aureus, mold and yeast counts), physical and chemical (pH, total acidity, ash, moisture, fat, protein, and carbohydrate) and sensory properties. The numbers of L. rhamnosus HN001 in samples stored at −20 °C for 120 days and 4 °C for 5 days were in the range of 7.43–7.67 log CFU/g and 7.47–7.61 log CFU/g, respectively ( P > 0.05). Probiotic added cheesecake samples had higher scores than control samples in terms of flavor, texture and general appreciation, depending on the storage time. The results of the study showed that L. rhamnosus HN001 can survive during storage period at levels higher than 6 log CFU/g. Consequently, cheesecake formulation used in this study had a food matrix suitable for the growth of L. rhamnosus HN001, which affects the sensory properties of the product in a positive way. Graphical abstract: Image 1 Highlights: Development of a probiotic cheesecake using L. rhamnosus in the formulation. The viability of L. rhamnosus was maintained during storage at both temperatures. The counts of L. rhamnosus decreased only the 5th days of storage at 4 °C (P < 0.05). Probiotic added cheesecake had high acceptability in terms of sensory properties.